2017
DOI: 10.15294/jtsp.v19i2.9646
|View full text |Cite
|
Sign up to set email alerts
|

Karakteristik Komposit Semen Limbah Partikel Bambu Dan Serat Aren Untuk Bahan Bangunan

Abstract: Kajian ini membahas karakteristik fisik dan mekanik komposoit semen limbah partikel bambu dan serat aren dengan variasi komposisi campuran untuk memperoleh formulasi empiris guna memprediksi sifat mekaniknya. Pembuatan dan pengujian benda uji dilakukan sesuai standar ASTM D 143 dengan 5 variasi komposisi jumlah campuran partikel bambu dan serat aren masing-masing 0%:100%; 25%:75%; 50%: 50%; 75%:25%; dan 100%: 0%; dengan kerapatan direncanakan 0,8 g/cm3. Variasi lainnya adalah ukuran limbah partikel bambu yaitu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
1
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 0 publications
0
1
0
1
Order By: Relevance
“…Penggunaan bambu saat ini sangat banyak digunakan dalam produk komposit sebagai konstruksi bangunan. Bambu memilki sifat yang tidak jauh berbeda dengan kayu dan bambu memiliki kekuatan tarik yang tinggi (Baskara et al, 2022); (Febrianto et al, 2017). Sementara pelepah aren memiliki serat partikel yang dapat diolah menjadi komposit.…”
Section: Pendahuluanunclassified
“…Penggunaan bambu saat ini sangat banyak digunakan dalam produk komposit sebagai konstruksi bangunan. Bambu memilki sifat yang tidak jauh berbeda dengan kayu dan bambu memiliki kekuatan tarik yang tinggi (Baskara et al, 2022); (Febrianto et al, 2017). Sementara pelepah aren memiliki serat partikel yang dapat diolah menjadi komposit.…”
Section: Pendahuluanunclassified
“…The density of each paving block is observed to decrease as the number of plastic melts increases. It can be attributed to the lower specific gravity of the plastic compared to that of the sand, resulting in a decrease in the volume weight (density) [21]. Moreover, The concrete's pores in paving blocks with a plastic mixture can also lead to a reduction in density between particles.…”
Section: Density Of Paving Blocksmentioning
confidence: 99%
“…Mercante et al [25] reported that adding plastic to a mortar reduced its compressive strength. This reduction in compressive strength can be caused by decreased density in the paving block mixture [21]. The smooth and slick plastic surface can weaken the aggregates' bond.…”
Section: Percent Of Plastic (%)mentioning
confidence: 99%
“…Bamboo is a plant that is well known to many Indonesian. Bamboo production in Indonesia in 2022 will be around 258.76 tons [10]. The potential for bamboo in Indonesia is quite large.…”
Section: Introductionmentioning
confidence: 99%